Implementation of SQ6R Learning Model to Improve Reading Comprehension of Algorithm on Basic Programming Subjects - Ranu Putra Wiyana; Basori Basori; Agus Efendi (Journal of Informatics and Vocational Education, 2019)
The purpose of this research is to improve students' reading comprehension of algorithm on basic programming subjects, especially on basic competence of branch control structure by using SQ6R learning model (Survey, Question, Read, Reflect, Review, Rehash, Rethink, Reevaluate). Research began with identifying problems that occured in the classroom. Then designed an action to overcome it in an action cycle. In this research the administration of action takes place in 2 cycles. Each cycle consists of the stages of planning, implementing, observing, and reflecting. The technique of data collection has been done through reading comprehension test of student and observation of learning activity. Analysis of the data was carried out using quantitative and qualitative analysis. The results showed that the SQ6R learning model can improve students' reading comprehension algorithm. This is indicated by the percentage of completeness of student learning outcomes by 38.9% in pre-cycle, 47.2% in cycle 1 and 83.3% in cycle 2.